Microporous polymeric composite membranes with advanced film properties: pore intercalation yields excellent CO2 separation performance. Issue 45 (2nd November 2018) - Sekizkardes, Ali K.; Kusuma, Victor A.; McNally, Joshua S.; Gidley, David W.; Resnik, Kevin; Venna, Surendar R.; Hopkinson, David
Abstract : PIM-1 based blend membranes with advanced gas transport and mechanical properties. Abstract : Polymers of intrinsic microporosity (PIMs) are revolutionary gas separation materials because of their ultra-high permeability, but suffer from low gas pair selectivity (for example CO2 /N2 ) and poor durability due to brittleness. Here we present a simple solution to these problems by blending PIM-1 with compatible polymer blend composed of PIM-1 and an ether side chain polyphosphazene (MEEP80), which possesses better mechanical flexibility and higher CO2 /N2 selectivity than the native PIM-1 while maintaining high CO2 permeability. Under mixed gas test conditions, a blend of 25 wt% MEEP80 in PIM-1 has a CO2 permeability of 2440 barrer and a CO2 /N2 selectivity of 39 under mixed gas testing conditions, putting it among the best known polymers for CO2 /N2 separation.